2020
DOI: 10.3390/tropicalmed5010026
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Public–Private Mix Model for Improving Tuberculosis Care in Vietnam: How Well Are We Doing?

Abstract: To improve tuberculosis (TB) care among individuals attending a private tertiary care hospital in Vietnam, an innovative private sector engagement model was implemented from June to December 2018. This included: (i) Active facility-based screening of all adults for TB symptoms (and chest x-ray (CXR) for those with symptoms) by trained and incentivized providers, with on-site diagnostic testing or transport of sputum samples, (ii) a mobile application to reduce dropout in the care cascade and (iii) enhanced fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Firstly, since TB diagnosis is the entry point into treatment and care, delays in diagnosis should be addressed by fostering collaborations between private and public healthcare sectors and alternative health providers such as traditional healers [ 42 , 54 ], investing resources into earlier diagnosis using rapid diagnostic technology, communicating current TB guidelines to all healthcare workers, raising community awareness about signs and symptoms of TB and benefits of early health seeking from public facilities. Secondly, given the health seeking patterns observed in this study and other studies [ 42 , 44 ], public-private partnerships may enhance TB case finding in Zimbabwe as has been demonstrated in Vietnam [ 55 , 56 ]. Private pharmacies and clinics will have to be trained on screening for TB and referral systems for sputum specimens to public health laboratories for TB testing.…”
Section: Discussionsupporting
confidence: 52%
“…Firstly, since TB diagnosis is the entry point into treatment and care, delays in diagnosis should be addressed by fostering collaborations between private and public healthcare sectors and alternative health providers such as traditional healers [ 42 , 54 ], investing resources into earlier diagnosis using rapid diagnostic technology, communicating current TB guidelines to all healthcare workers, raising community awareness about signs and symptoms of TB and benefits of early health seeking from public facilities. Secondly, given the health seeking patterns observed in this study and other studies [ 42 , 44 ], public-private partnerships may enhance TB case finding in Zimbabwe as has been demonstrated in Vietnam [ 55 , 56 ]. Private pharmacies and clinics will have to be trained on screening for TB and referral systems for sputum specimens to public health laboratories for TB testing.…”
Section: Discussionsupporting
confidence: 52%
“…Regarding the outcome ‘improved efficiency’, high TB treatment initiation was consistently reported across both model types (41, 52, 53, 81). Studies also reported lower loss to follow-up before treatment initiation among PPM PPs compared to non-PPM PPs (43).…”
Section: Resultsmentioning
confidence: 93%
“…For eight studies (27, 28, 33, 34, 48, 49, 57, 58, 60, 61, 70, 71, 84, 85, 87, 88), the research was reported across two publications each, which were merged and extracted as one study (Table 1 and Appendix 6). Most studies were from the WHO South-East Asia region (n=36, 65.4%) (30, 33, 36, 37, 4042, 45, 47, 48, 50, 51, 54–56, 59, 60, 62, 6467, 69, 7476, 7884, 86, 87, 89), followed by Eastern Mediterranean (n=7, 12.7%) (32, 43, 44, 46, 72, 73, 77), Western Pacific (n=6, 10.9%) (27, 31, 35, 52, 57, 70), African (n=4, 7.3%) (38, 39, 53, 68), and American (n=1, 1.8%) (63) regions. One study reported models from across three different countries and regions (29).…”
Section: Resultsmentioning
confidence: 99%
“…They added a mobile application to reduce dropouts in the cascade of care. This showed high rates of uptake in investigations by persons with possible symptoms of TB and of treatment by those diagnosed with TB [ 7 ]. In another study from Vietnam, Vo et al showed an increase of 8.5% in all forms of TB notifications through subsidized CXR screening and Xpert MTB/RIF testing among private practitioners, with support of improved reporting to the national TB program [ 8 ].…”
mentioning
confidence: 99%